Challenges of private retirement scheme (PRS) in Malaysia - Mohd Ali @ Ramli, Azlin Namili; Yeon, Asmah Laili; Hussain, Mohammad Azam (2015)
This paper intend to compare and analyse the private retirement scheme (PRS) and other retirement schemes that exists in Malaysia.PRS is a complementary scheme to the existing Malaysian pension schemes that are Government Pension Scheme (GPS) and Employees Provident Fund (EPF).There are many differences between the three retirement schemes such as the dividend in EPF is guaranteed, the government servant will received their pension after retirement but PRS depend solely on the investment made by contributor; EPF and GPS give death and incapacitation benefits to their members but not PRS; income tax relief are given to PRS contributor and EPF members.These differences lead to challenges in providing PRS to contributors especially during the economic downturn faced by our country today.